PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN TENTANG ORGANISASI DI SEKOLAH DAN MASYARAKAT MELALUI PENERAPAN METODE BELAJAR PINTAR SISWA KELAS V SDN 1 TUGU KECAMATAN MLARAK KABUPATEN PONOROGO SEMESTER II TAHUN PELAJARAN 2012/2013 - Hastuti, Endang Puji (Educatio Vitae, 2016)
This study reeexamines not only the dimensions of achievement but also special materials.It analyses to stimulating student activity in effectiveness study methods with variety joyfull learning activity. This study also shows the result of study citizenship to mentioned several organisation at  their surrounding environtment which obserbving the potentially.It means that studying organisation of  citizenship must consider the characteristics is based observing students surrounding environtment potentially.The result indicates belajar pintar methods can stimulating student to increasing interest to learn several organisation of citizenship. Key Words : Result of Study. Belajar Pintar Methods. Problem solving